Religiosity, Family Environment, Motivation, and Entrepreneurial Interest: The Mediating Role of Self-Efficacy among Former Indonesian Migrants - Hansen Rusliani; Rokhmat Subagiyo; Asyma Salsabila; Muhammad Raisa Haqqiquddin Rokhmatulloh; Nur Kholis; Binti Nur Asiyah (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2026)
The objective of this research is to examine how religiosity, family environment, and motivation affect entrepreneurial interest mediated by self-efficacy among ex-Indonesian migrant workers in Tulungagung Regency. A quantitative approach was used in this research, collecting primary data through questionnaires from 135 randomly selected respondents. Data analysis was carried out using the Partial Least Squares (PLS) method, processed with the aid of WarpPLS software version 8.0. The study reveals that religiosity and motivation have a substantial impact on self-efficacy and entrepreneurial interest. At the same time, the family environment does not significantly influence entrepreneurial interest through self-efficacy.